DOES ISLAMIC FINANCIAL LITERACY PROVIDE YOUNG FAMILIES' FINANCIAL RESILIENCE IN THE POST COVID-19 ERA? - Afif Zaerofi; Shofi Arofatul Marits (Faculty of Islamic Business and Management, 2025)
This study, conducted with a quantitative research approach, aimed to examine the factors influencing Islamic financial literacy and financial behavior, and their subsequent impact on financial resilience among young couples post-COVID-19. Employing Structural Equation Model-Partial Least Squares (SEM-PLS), the research analyzed data collected through questionnaires from a total of 250 respondents. The findings suggested Islamic Financial Literacy has both positive effects on Financial Resilience. and Islamic Financial Behavior. Interestingly, Risk Tolerance Level has a negative effect on Islamic Financial Behavior. In addition, Financial Behavior has a positive effect on Financial Resilience.